EXPLORING DENTISTS' KNOWLEDGE AND PERSPECTIVES ON ORALBIOPSIES AT BAQAI DENTAL COLLEGE, KARACHI - Samara Rais; Nauman Sheikh; Zarah Subhan; Qasim Saleem; Ayesha Azmat; Ramsha Tariq (Baqai Journal of Health Sciences)
Background: Oral biopsy is an essential diagnostic tool for identifying a range of oral lesions, from benign conditions to malignancies. Despite its significance, gaps in knowledge and practice among dentists may hinder its effective utilization, impacting patient outcomes.